Hubungan Efikasi Menyusui dengan Depresi Postpartum - Bulan Syitazahra; Niken Sukesi (Journal of Educational Innovation and Public Health, 2026)
The postpartum period is a critical transitional phase during which women are vulnerable to psychological disturbances, particularly postpartum depression. Psychological distress may undermine maternal confidence, including the perceived ability to breastfeed effectively. This study aimed to examine the relationship between breastfeeding self-efficacy and postpartum depression among postpartum mothers. A quantitative cross-sectional design was employed involving 45 respondents selected through total sampling. Depressive symptoms were assessed using the Edinburgh Postnatal Depression Scale (EPDS), while breastfeeding self-efficacy was measured using the Breastfeeding Self-Efficacy Scale-Short Form (BSE-SF). Data were analyzed using Spearman’s Rank correlation test with a significance level of 0.05. The results demonstrated a statistically significant and strong negative correlation between breastfeeding self-efficacy and postpartum depression (r = –0.616; p < 0.05). Mothers with higher depressive symptoms tended to report lower levels of breastfeeding self-efficacy. These findings highlight the importance of integrating mental health screening and breastfeeding support into postpartum care to strengthen maternal confidence and improve breastfeeding outcomes.